2016
DOI: 10.1212/wnl.0000000000003428
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic stroke subtypes and migraine with visual aura in the ARIC study

Abstract: Objective: To investigate the association among migraine, ischemic stroke, and stroke subtypes in the Atherosclerosis Risk in Communities (ARIC) study.Methods: In this ongoing, prospective, longitudinal community-based cohort study, participants were given an interview ascertaining migraine history in 1993-1995, and were followed for all vascular events, including stroke. All stroke events over the subsequent 20 years were adjudicated and classified into stroke subtypes by standard definitions. Cox proportiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 33 publications
1
47
0
Order By: Relevance
“…Several case-control and cohort studies, as well as pooled data analyses, indicate that migraine is a risk factor for stroke and other vascular events [ 1 6 ]. Most of the evidence supports an increased risk of ischemic stroke associated with migraine with aura [ 7 18 ]. For migraine without aura, the interpretation of available data is more complex as some studies reported that migraine without aura is also associated with an increased risk of ischemic stroke [ 10 , 18 , 19 ] whereas in others the association was not confirmed [ 7 , 11 , 15 , 16 ].…”
mentioning
confidence: 99%
“…Several case-control and cohort studies, as well as pooled data analyses, indicate that migraine is a risk factor for stroke and other vascular events [ 1 6 ]. Most of the evidence supports an increased risk of ischemic stroke associated with migraine with aura [ 7 18 ]. For migraine without aura, the interpretation of available data is more complex as some studies reported that migraine without aura is also associated with an increased risk of ischemic stroke [ 10 , 18 , 19 ] whereas in others the association was not confirmed [ 7 , 11 , 15 , 16 ].…”
mentioning
confidence: 99%
“…In the ARIC study, migraine with visual aura was associated with cardioembolic stroke (HR 1.7; 95% CI: 1.2‐2.6, P = .008), but not with thrombotic or lacunar subtypes, suggesting visual aura symptoms may be related to distal emboli in the posterior circulation 154 . The study also reported that MWA was associated with increased risk of new onset atrial fibrillation, an important stroke risk factor in the aged 155 .…”
Section: Potential Mechanisms Of Migraine‐related Strokementioning
confidence: 92%
“…4 The increased incidence of atrial fibrillation and cardioembolism in patients diagnosed with migraine with aura was linked to acute stroke. 5,6 Migraine with aura can also be found as a stroke mimic during acute stroke management 7 ; however, only a few studies investigated the frequency and characteristics of migraine with aura in patients who initially presented with strokelike symptoms.…”
mentioning
confidence: 99%
“…4 Recent studies showed that migraine with aurainduced stroke may be associated with an increased risk of incidental atrial fibrillation and cardioembolic stroke. 5,6 Because we included patients diagnosed with migraine with aura who initially presented with stroke-like symptoms, all patients underwent ECG and multimodal CT scan, and more than half patients underwent DWI MRI. We found no patients with perfusion change or asymptomatic ischemic stroke.…”
mentioning
confidence: 99%